Mechanical characterization of the stainless steel welds for the JT-60SA Cryostat Vessel Body Cylindrical Section. (March 2022) - Medrano, Mercedes; Serrano, Marta; Hernández, Rebeca; Plaza, Daniel; Muñoz, Antonio; Rincón, Esther; Cabrera, Santiago; Soleto, Alfonso; Pereira, Augusto; Alén, Cristina
Highlights: Mechanical characterization of the stainless steel welds for the JT-60SA Cryostat Vessel Body Cylindrical Section (CVBCS) aimed to its validation as part of the manufacturing phase. Results of the test programme carried out at Ciemat are presented: Microstructure analysis, hardness tests, Tensile tests (at RT and −60 °C), Charpy tests (at RT and −196 °C). Global results showed good behavior of the welds. Abstract: JT-60SA is the superconducting tokamak that will be operated at the Naka Fusion Institute of QST (the National Institutes for Quantum and Radiological Science and Technology) in Japan. The project is being developed under the framework of the Broader Approach Agreement between the EU and Japan (started in 2007) for an early realization of the fusion energy, aimed at conducting supportive and complementary work for the ITER experimental program towards DEMO. The assembly of the tokamak components as well as the related equipment was completed last year and the device is currently undergoing the integrated commissioning phase. Within the European contribution, Spain was one of the stakeholders that committed it, as a Voluntary Contributor, to design and manufacture one of the main components of the device: the cryostat. The cryostat is a large stainless steel vacuum vessel, 14 m diameter, 16 m high, which encloses the tokamak and provides the vacuum boundary (10 −3 Pa) necessary to limit the heat loads on the magnets operated at cryogenic temperatures. The component is made up of the Cryostat Base (CB), the Cryostat Vessel Body Cylindrical Section (CVBCS), both designed and fabricated in Spain (through the National Fusion Laboratory at Ciemat), as well as the cryostat top lid (CTL) designed and procured by Japan (through QST). Within the manufacturing phases of the CB and CVBCS an extensive test program was carried out at Ciemat that focussed on the characterization of the welding processes selected for the manufacturing before their final approval. The aim of this paper is to present the results of the mechanical and microstructural tests performed on the welded joints.